1994
DOI: 10.1136/hrt.72.2.128
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral vascular disease: consequence for survival and association with risk factors in the Speedwell prospective heart disease study.

Abstract: Objective-To measure the prevalence and incidence of intermittent claudication, to describe the mortality associated with the condition, and to assess the relevance of risk factors for vascular disease. Design-A standard questionnaire on calf pain when walking was given in the prospective Speedwell study, and a range of risk factors were measured. The men were re-examined at intervals of three years, and deaths over 11 years were identified. Setting-The general population. Participants-All men aged 45 to 59 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(82 citation statements)
references
References 12 publications
(3 reference statements)
1
78
0
3
Order By: Relevance
“…26,27 The discrepancy may be related to the higher prevalence of PAD in elderly males and in smokers; elderly males show a weaker relationship between obesity and CVD, and smokers tend to have lower BMI than non-smokers. 28 A recent prospective cohort study revealed a positive relationship between waist-to-hip ratio, not BMI, and PAD prevalence.…”
Section: Peripheral Arterial Disease (Pad)mentioning
confidence: 96%
“…26,27 The discrepancy may be related to the higher prevalence of PAD in elderly males and in smokers; elderly males show a weaker relationship between obesity and CVD, and smokers tend to have lower BMI than non-smokers. 28 A recent prospective cohort study revealed a positive relationship between waist-to-hip ratio, not BMI, and PAD prevalence.…”
Section: Peripheral Arterial Disease (Pad)mentioning
confidence: 96%
“…Very few prospective studies have focused on the relation between triglycerides and peripheral vascular disease. The most common feature of PAD is raised levels of triglycerides and lower levels of high-density lipoprotein (HDL) cholesterol as compared with age-and sexmatched controls without vascular disease, with similar levels of cholesterol and low-density lipoprotein (LDL) cholesterol [43][44][45][46][47] . The frequency of a cluster of lipid abnormalities of the type of raised triglycerides and small and dense LDL and reduced HDL was 20% in persons with PAD vs 0% in the control group [48] .…”
Section: Fasting Lipids In Padmentioning
confidence: 99%
“…Prospective studies have established tobacco consumption, diabetes, elevated blood pressure and cholesterol levels as the main predisposing factors to intermittent claudication (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(20)(21)(22). In most studies, tobacco consumption was the dominant risk factor.…”
Section: Discussionmentioning
confidence: 99%